Peran Media Sosial dalam Mendorong Perilaku Konsumen terhadap Boikot Produk Israel - Darlin Rizki; Fikriya Aniqa Fitri; Nisa Ulmuftia (Universitas Muhammadiyah Mataram, 2025)
Abstract: The focus of this study is on consumer behavior and the economic consequences of the boycott campaign against Israeli products in Indonesia. This research adopts a qualitative approach to analyze consumer responses to the boycott movement that has spread across social media. Data were collected through documentation from various information platforms such as books, journals, reports, magazines, newspapers, and others. The findings reveal that consumer behavior is influenced by the boycott movement, particularly in terms of product and brand choices. Consumers are largely influenced by their religious beliefs, cultural values, and ethnocentric views toward certain products. Moreover, social media plays a significant role in disseminating information and supporting the boycott movement. The economic impact analysis of the boycott includes the potential decline in sales and how companies respond to consumer pressure. The extent to which this movement will affect Indonesia’s overall economy remains a subject of debate, although it may exert considerable pressure on targeted companies. This study provides deeper insight into the complexity of the phenomena caused by the boycott campaign of Israeli products in Indonesia. It is crucial to thoroughly consider both the economic impact and changes in consumer behavior at local and international levels.Abstrak: Fokus penelitian ini adalah perilaku konsumen dan konsekuensi ekonomi dari kampanye boikot produk Israel di Indonesia. Penelitian ini menggunakan pendekatan kualitatif untuk menganalisis respons konsumen terhadap gerakan boikot yang tersebar di media sosial. Data dikumpulkan dengan cara dokumentasi di perbagai platform informasi seperti buku, jurnal, laporan, majalah, koran, dan lain sebagainnya. Hasil penelitian menunjukkan bahwa perilaku konsumen dipengaruhi oleh gerakan boikot, terutama dalam hal memilih produk dan merek. Konsumen banyak dipengaruhi oleh agama, budaya, dan pandangan etnosentris mereka tentang produk tertentu. Selain itu, media sosial sangat penting untuk menyebarkan informasi dan mendukung gerakan boikot. Selain itu, analisis dampak ekonomi gerakan boikot mencakup potensi penurunan penjualan dan bagaimana perusahaan menanggapi tekanan konsumen. Bagaimana gerakan ini akan berdampak pada ekonomi Indonesia secara keseluruhan masih diperdebatkan, meskipun dapat menempatkan tekanan besar pada perusahaan yang menjadi sasaran. Dengan penelitian ini, kita dapat lebih memahami lebih lanjut tentang kompleksitas fenomena yang disebabkan oleh kampanye boikot produk Israel di Indonesia. Sangat penting untuk mempertimbangkan dampak ekonomi dan perubahan perilaku konsumen secara menyeluruh, baik di tingkat lokal maupun internasional.